The influence of ageing on martensite ordering and stabilization in shape memory Cu-Al-Ni alloys - Aydogdu, A; Aydogdu, Y; Adiguzel, O (Pergamon-Elsevier Science Ltd, 1997)
The martensitic transformation and the associated mechanical shape reversibility in copper-based shape memory alloys is strongly influenced by quenching and ageing treatments. Ageing of martensite in as-quenched Cu-Al-Ni alloys can result in loss of memory behavior. Structural studies have been carried out to measure the changes in the degree of order that develop during martensitic ageing of two Cu-Al-Ni alloys. Stabilization is directly related to disordering in martensitic state and the spacing differences (Delta d) between selected pairs of diffraction planes reflect the degree of ordering in martensite. The changes in degree of order are shown to be similar in as-quenched and post-quenched beta-phase annealed alloys, thereby leading to the conclusion that loss of memory in as-quenched alloys is not solely attributable to any extra changes in degree of order brought about by excess vacancies during martensitic ageing. Copyright (C) 1997 Elsevier Science Ltd.
Keywords: alloys; X-ray diffraction; crystal structure